Vitamin D Supplementation, Serum 25(OH)D Concentrations and Cardiovascular Disease Risk Factors: A Systematic Review and Meta-Analysis - Mirhosseini, Naghmeh; Rainsbury, Jacqueline; Kimball, Samantha M. (Frontiers in Cardiovascular Medicine, 2018)
Background: Cardiovascular disease (CVD) risk factors are associated with low serum 25 hydroxyvitamin D (25(OH)D) concentrations in observational studies; however, clinical trial findings are inconsistent. Objective: We assessed the effect of vitamin D supplementation and increased serum 25(OH)D concentrations on CVD risk factors in a systemic review and meta-analysis of randomized controlled trials (RCTs). Design: MEDLINE, CINAHL, EMBASE and Google Scholar were searched for RCTs that evaluated vitamin D supplementation and cardiovascular outcomes [blood pressure, parathyroid hormone (PTH), serum high-sensitivity C-reactive protein (hs-CRP), total cholesterol, high and low density lipoprotein (HDL and LDL, respectively), triglycerides, peak wave velocity (PWV) and Augmentation Index (AI)] from 1992 through 2017. Meta-analysis was based on a random-effects model and inverse variance method to calculate standardized mean difference (SMD) as effect sizes, followed by a leave-one-out method for sensitivity analysis. Risk of publication bias was assessed using Cochrane checklist and Begg funnel plots. The systematic review is registered as CRD42015025346. Results: We identified 2341 studies from which 81 met inclusion criteria. The meta-analysis indicated a significant reduction in systolic blood pressure (SMD=-0.102±0.04 mmHg, 95% confidence interval (CI), -0.20 to -0.03), diastolic blood pressure (SMD=-0.07±0.03 mmHg, 95% CI, -0.14 to -0.006), serum PTH (SMD=-0.66±0.08 ng/L, 95% CI, -0.82 to -0.49), hs-CRP (SMD=-0.20±0.07 mg/L, 95% CI, -0.34 to -0.06), total cholesterol (SMD=-0.15±0.06 mmol/L, 95% CI, -0.25 to -0.04), LDL (SMD=-0.10±0.05 mmol/L, 95% CI, -0.20 to -0.003), triglycerides (SMD=-0.12±0.06 mmol/L, 95% CI, -0.23 to -0.003) and a significant increase in HDL (SMD=0.09±0.04 mmol/L, 95% CI, 0.00 to 0.17) with vitamin D supplementation. These findings remained significant in sensitivity analyses for blood pressure, lipid profile, serum PTH, and serum hs-CRP. There was no significant effect of vitamin D supplementation on PWV (SMD=-0.20±0.13 m/s, 95% CI, -0.46 to 0.06, p=0.14) and AI (SMD=-0.09%±0.14%, 95% CI, -0.37 to 0.19, p=0.52) for vitamin D supplemented groups. Conclusion: These findings suggest that vitamin D supplementation may act to protect against CVD through improving risk factors, including high blood pressure, elevated PTH, dyslipidemia, and inflammation.